Prospective Evaluation of Utilization Patterns and Prescribing Guidelines of Opioid Consumption Following Orthopedic Foot and Ankle Surgery. (November 2018) - Saini, Sundeep; McDonald, Elizabeth L.; Shakked, Rachel; Nicholson, Kristen; Rogero, Ryan; Chapter, Megan; Winters, Brian S.; Pedowitz, David I.; Raikin, Steven M.; Daniel, Joseph N.
Background: Overprescription of narcotic pain medication is a major culprit in the present opioid epidemic plaguing the United States. The current literature on lower extremity opioid usage has limitations and would benefit from additional study. The purpose of our study was to prospectively assess opioid consumption patterns following outpatient orthopedic foot and ankle procedures. Methods: Patients undergoing outpatient orthopedic foot and ankle procedures who met inclusion criteria had the following prospective information collected: patient demographics, preoperative health history, patient-reported outcomes, anesthesia type, procedure type, opioid prescription and consumption details. The morphine equivalent dose was calculated for each prescription and then converted to the equivalent of a 5-mg oxycodone "pill." Univariable analyses were performed to identify variables with a statistically robust association with opioid consumption for inclusion in a multivariable linear regression. A stepwise backward regression was then performed to identify independent predictors of opioid consumption. Postoperative opioid utilization was reported for 988 patients (mean age: 49 years). Results: Overall, patients consumed a median of 20 pills whereas the median number of pills prescribed was 40. This resulted in a utilization rate of 50% and 20 631 pills left unused. Independent factors associated with higher opioid consumption were anesthesia type ( P < .004), age <60 years ( P < .001), preoperative visual analog scale (VAS) pain report of >6 ( P = .008), and bony procedures ( P = .008); residual standard error 16.73 ( F 7, 844 =14.3, P < .001). Conclusion: Our study found that patients who underwent orthopedic foot and ankle procedures were overprescribed narcotic medication by nearly twice the amount that was actually consumed. Although we identified 4 independent factors associated with opioid consumption, the large residual standard error suggests that there remains a substantial degree of unexplained variance of opioid consumption observed in the patient population. Physicians face a challenging task of setting appropriate protocols when balancing pain relief and generalizable guidelines. Level of Evidence: Level II, prospective observational cohort study.